Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and the risk of early-onset post-stroke depression: a prospective study - Deng, Mingzhu; Song, Kangping; Gao, Lichen; Wang, Zhen; Zhao, Wei; Xu, Wei; Feng, Tieqiao; Li, Fangyi (Frontiers in Neurology, 2025)
BackgroundThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a recently emerging composite biomarker of atherogenic lipid metabolism. However, the relationship between NHHR and early-onset post-stroke depression (PSD) remains underexplored.MethodsEarly-onset PSD was diagnosed 2 weeks after an acute ischemic stroke (AIS). Depression severity was assessed using the Hamilton Depression Scale-17 items (HAMD-17). Patients with scores ≥7 were classified into the early-onset PSD group. Spearman rank correlation analysis was used to examine the relationship between NHHR and HAMD scores. Logistic regression analysis was conducted to evaluate the association between NHHR and early-onset PSD. Sensitivity analyses were performed to assess the robustness of the results. The predictive performance of NHHR for early-onset PSD was evaluated using receiver operating characteristic curve (ROC) analysis.ResultsAmong 846 prospectively enrolled patients, 283 (33.45%) were diagnosed with early-onset PSD. NHHR was positively correlated with HAMD-17 scores (r = 0.498, p < 0.001). Binary logistic regression indicated that NHHR (odds ratio [OR], 1.796; 95% confidence interval [CI] 1.452–1.996, p < 0.001) was an independent risk factor for early-onset PSD. The area under the curve (AUC) for NHHR in predicting early-onset PSD was 0.798.ConclusionThe findings suggest that NHHR may serve as an independent risk factor for early-onset PSD, providing valuable insights for preventive strategies and prognostic management in these patients.